Product Innovation of Taro Croquette with Moringa Leaves and Oyster Mushroom Stuffing - Fatimah Nur Hanifah Nasution; Christian H. Rumayar; Dias Pratami Putri (Gastronomy Tourism Journal, 2022)
Product innovation in food is one aspect of improving an existing food product, especially the health benefits in it so that it can be consumed by anyone without worrying about side effects due to unhealthy food. Croquettes are a potato-based snack filled with various kinds of meat, so croquettes cannot be enjoyed by vegetarians. Therefore, an innovative product of taro croquettes was made with the stuffing of moringa leaves and oyster mushrooms. Croquettes made from taro which is one of the local foods whose products must be reproduced and developed, then using the stuffing of oyster mushrooms and moringa leaves which is one of the superfoods that has very good nutritional value so that it can increase the value of the croquettes,. Therefore, many people can try taro croquettes with moringa leaves and oyster mushrooms as a healthier option. This research employs a quantitative research method through an experimental approach. In the taro croquette product innovation experiment, there were three recipe formulations that were tested by expert panelists and general panelists so that the test results could produce the best recipe formulation among the three formulations that had been made.